Penentuan Kadar Fenolik Total dan Uji Antioksidan Kombinasi Ekstrak Daun Kecibeling (Strobilanthes crispa (L.) Blume) dan Daun Pepaya (Carica papaya L.) - Melindra Mulia; Dedek Fitriani (Lembaga Yasin AlSys, 2025)
The limited number of studies on the synergistic antioxidant potential of combined extracts from Kecibeling leaves (Strobilanthes crispa (L.) Blume) and Papaya leaves (Carica papaya L.) forms the basis of this research, despite its significant implications for the development of safe natural antioxidant products. This study aims to determine the total phenolic content and evaluate the antioxidant activity of various combination ratios of Kecibeling and Papaya leaf extracts. A quantitative experimental approach was employed, using maceration extraction with 96% ethanol as the solvent. Data were obtained through the Folin–Ciocalteu assay to determine total phenolic content and the DPPH method to assess antioxidant activity, analyzed via spectrophotometry and linear regression to calculate IC₅₀ values. The results show that the 75:25 ratio (Kecibeling:Papaya) yielded the highest total phenolic content at 71.35 mg GAE/g and exhibited the strongest antioxidant activity with an IC₅₀ value of 62.02 µg/mL, categorized as a strong antioxidant. These findings support the theory that combining phenolic compounds from different plant sources can enhance their biological activity. Thus, the combination of Kecibeling and Papaya leaf extracts proved superior to single extracts in terms of antioxidant efficacy. The implications of this study include contributions to the literature on phytochemical synergy and practical recommendations for the herbal and functional food industries in formulating natural ingredient combinations.